Literatur Review : Gambaran Kecemasan dan Perilaku Pencegahan Covid-19 pada Ibu Hamil Selama Pandemik: Literature Review: The Relationship of Anxiety and COVID-19 Prevention Behavior in Pregnant Women During a Pandemic - Tina Mawardika; Umi Aniroh; Alvina Rossida (Journal of Holistics and Health Sciences (JHHS), 2022)
The number of pregnant women with COVID-19 contributed 0,24% of the number of COVID-19 cases. The implementation of COVID-19 prevention in pregnant women, in the community, including universal precautions, has not gone as expected. This is possible due to excessive factors in the COVID-19 pandemic. To determine the relationship between the prevention of COVID-19 in pregnant women during the pandemic. This research design is literature review. The secondary data source is in the form of articles taken from three databases (PubMed, ProQuest and Google Scholar). The criterion articles that are reviewed are the maximum journal publication time span of 5 years, in Indonesian and English, original articles and available full text. The articles that are eligible for review are 14 articles, namely four in Indonesian and ten in English. Anxiety in pregnant women during the COVID-19 pandemic, most of the categories anxious with category mild, moderate and very heavy. Most of the preventive behaviors in pregnant women during the COVID-19 pandemic were in good or high categories. Anxiety related to the prevention of COVID-19 in pregnant women. pregnant women should increase their understanding of COVID-19 prevention by actively deleting literature or measuring health workers by telephone so that they can reduce understanding and increase prevention. ABSTRAK Jumlah wanita hamil dengan COVID-19 ini menyumbangkan 0,24% angka kasus COVID-19. Pelaksanaan pencegahan COVID-19 pada ibu hamil, di masyarakat meliputi universal precaution belum berjalan sesuai harapan. Hal tersebut dimungkinkan karena faktor kecemasan yang berlebihan dari ibu hamil terhadap pandemic COVID-19. Mengetahui gambaran kecemasan dan perilaku pencegahan COVID-19 pada Ibu Hamil Selama Pandemik. Desain penelitian ini literature review. Sumber data sekunder berupa artikel diambil dari tiga data base (PubMed, ProQuest serta Google Scholar). Kriterian artikel yang di review yaitu rentang waktu penerbitan jurnal maksimal 5 tahun, berbahasa Indonesia dan Inggris, original artikel dan tersedia full teks. Artikel yang layak untuk di review sebanyak 14 artikel yaitu empat berbahasa Indonesia dan sepuluh artikel berbahasa Inggris. Kecemasan pada ibu hamil selama pandemik COVID-19, sebagian besar mengalami cemas (71,4%) dengan kategori ringan (21,6%), sedang (23,6%) dan sangat berat (6,1%). Perilaku pencegahan pada ibu hamil selama pandemik COVID-19, sebagian besar mempunyai kategori baik (69,2%). Kecemasan berhubungan dengan perilaku pencegahan COVID-19 pada ibu hamil. sebaiknya masyarakat meningkatkan pemahaman tentang pencegahan COVID-19 dengan aktif berkonsultasi dengan tenaga kesehatan via telefon sehingga dapat meningkatkan pencegahan.